US bank lending to small businesses: an analysis of covid-19 and the paycheck protection program - Abugri, Benjamin A.; Osah, Theophilus T. (Journal of Risk and Financial Management, 2025)
This paper examines the characteristics of banks and their lending behavior in relation to Paycheck Protection Program (PPP) loans and commercial and industrial (C&I) loans to small businesses during the COVID-19 pandemic. Our findings show that lenders facing greater risk tended to lend more PPP loans, consistent with the risk-aversion theory. Specifically, banks with a higher loan–deposit ratio, lower overall profitability, poorer loan quality, and higher exposure to risks in business (C&I) loans are characterized by higher PPP loans. C&I loans to all businesses are negatively related to the loan–deposit ratio and loan loss allowance ratio, but are positively linked with the capital ratio. However, we find important differences in C&I lending to small businesses versus large businesses. Furthermore, there is evidence regarding the success of targeting PPP loans towards more productive sectors of the US economy. Using FDIC-defined banks’ lending specializations, we show that banks focused on international lending had a limited role in PPP lending.
Keywords: 2019-20 coronavirus outbreak; Business; COVID-19 pandemic; Coronavirus disease 2019 (COVID-19); Medicine; Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); US banks; Virology; commercial and industrial loans; dept.fin; paycheck protection program; peer-reviewed; risk aversion; small business lending

Derivative use, ownership structure and lending activities of US banks - Abugri, Benjamin A; Osah, Theophilus Teye (Journal of Economics and Finance, 2021)
Following the 2007–2008 financial crisis, there is widespread interest in understanding how derivative use drives bank lending behavior. Our paper examines the impact of bank ownership structure on the relationship between derivative use and lending activities of U.S. banks. We find that lending recovered faster in larger banks than smaller banks post-crisis and in line with Diamond’s (Diamond DW 1984 Financial intermediation and delegated monitoring. Rev Econ Stud 51:393–414) systemic risk reduction theory, derivative use is positively associated with lending growth. Ownership is significant in explaining the magnitude of the relationship even after controlling for alternative specifications of the derivative use variable. In both normal and crisis periods, the speed of adjustment of lending to derivatives use by stock banks lags that of mutual banks. We suggest that speculative trading in derivatives substitutes for lending growth to a larger extent for stock banks compared to mutual banks. These findings may have important implications for investors and bank regulators. © 2020, Academy of Economics and Finance.
Keywords: dept.eco; dept.fin; peer-reviewed

Board Characteristics and performance of listed firms in Ghana - Andoh, Jennifer A.N.; Abugri, Benjamin A.; Anarfo, Ebenezer B. (Corporate Governance: The International Journal of Business in Society, 2022)
Purpose This study aims to compare the impact of board characteristics on the performance of listed non-financial firms to the impact of board characteristics on the performance of listed financial firms (commercial banks) in Ghana. Design/methodology/approach The fixed and random effects models with generalized least square specifications are used in estimating regressions to correct for heteroscedasticity and serial correlation. Additionally, this study uses lagged models of the board variables to address the possibility of the presence of endogeneity and to generate robust estimates. Findings The empirical results show some similarities and differences on the impact of board characteristics on the performance of listed non-financial firms and banks. On similarities, for both non-financial firms and banks, board size is seen to have a significant non-linear impact on Tobin’s q. Also, the proportion of foreign board members shows a positively significant relationship with firm performance for both listed non-financial firms and banks. The effect of the proportion of board members with higher educational qualifications on firm performance appears to be negative and statistically significant for both sample of firms. On the other hand, the impact of board composition and board gender diversity on firm performance differs from listed banks and non-financial firms. Research limitations/implications The panel regressions for the listed banks were run on 63 observations because of the small sample size for the listed banks. Though enough for estimation purposes, inferences from results should be made with caution. Originality/value This paper, unlike most corporate governance – firm performance studies, focuses not only on listed non-financial firms but also on listed banks. From a multi-theoretical perspective, this paper provides a comparative analysis on the impact of board characteristics on financial performance of listed non-financial firms and banks.
Keywords: Banks; Board characteristics; Firm performance; Ghana; Non-financial firms; dept.fin; peer-reviewed